The videomaniac - Mara, Wil (Mara, Wil. Twisted., 2019)
"At a local flea market, thirteen-year-old Brian Hart meets a creepy old man who gives him computer software that can predict future NFL games. But is the power to see the future really as beneficial as Brian believes?"--Back cover.